Plasma matrix metalloproteinase‐3 correlates with the clinical severity in men with multiple system atrophy. Issue 2 (26th March 2013) - Sasaki, Hidenao; Matsushima, Masaaki; Hama, Yuka; Sakushima, Ken; Nakamura, Masakazu; Yabe, Ichiro; Oba, Koji; Tanji, Kunikazu; Mori, Fumiaki; Wakabayashi, Koichi; Kakita, Akiyoshi; Takahashi, Hitoshi; et al.
Abstract Aim Matrix metalloproteinase‐3 (MMP‐3), MMP‐9 and tissue inhibitor of matrix metalloproteinase‐1 (TIMP‐1) play roles in remodeling and repairing tissue. The aim of the present study was to investigate correlations between plasma levels of these proteins and clinical severity of multiple system atrophy (MSA). Methods MMP‐3, MMP‐9 and TIMP‐1 levels were measured by enzyme‐linked immunosorbent assay (ELISA) in 72 MSA patients and 48 adult controls. Clinical severity was rated with the scale for assessing and rating ataxia (SARA) and the unified MSA rating scale (UMSARS). Immunohistochemistry and immunoblotting were used to assess MMP‐3 expression in post‐mortem brain tissue. Results Plasma MMP‐3 was significantly lower in females than males, but MMP‐9 and TIMP‐1 showed no sex difference. Compared with age‐matched controls (age ≥40 years), male MSA patients had significantly lower plasma MMP‐3, but no difference was detected in female MSA patients versus controls. We observed significant correlations with rating scales in male, but not female, patients; plasma TIMP‐1 positively correlated with SARA and UMSARS, whereas plasma MMP‐3 showed an inverse correlation with the rating scales. These correlations became more evident when the MMP‐3/TIMP‐1 ratio was used as an index. Plasma MMP‐9 did not correlate with any scales in male patients, but was positively correlated with UMSARS in female patients. Immunohistochemical studies of post‐mortem brain tissues showed that total cerebellar MMP‐3 expression was not significantly different between MSA patients and controls, but glial cytoplasmic inclusions were intensely immunoreactive for MMP‐3. Conclusion MMP‐3 and TIMP‐1 are possible biomarker candidates for MSA. However, it is unclear whether they accurately reflect clinical progression.